Genomic Modifiers of Neurological Resilience in a Niemann-Pick C Family - Cubillos-Riffo, F (John Wiley and Sons Inc, 2025)
Niemann-Pick type C (NPC) disease, caused by NPC1 or NPC2 variants, disrupts cholesterol and glycolipid trafficking, leading to diverse clinical manifestations. To understand the genetic basis of neurological resilience, we analyzed an NPC family with variable phenotypes, identifying loss-of-function variants in CCDC115, SLC4A5, DEPDC5, ETFDH, SNRNP200, and DOCK1 that co-segregated with milder neurological involvement. Using yeast models, we successfully predicted NPC-like severity based on orthologous gene variants. RNA-seq revealed a positive correlation between mitochondrial transcripts and cellular fitness. Modeling NPC in yeast lacking the SLC4A5 ortholog, bor1, enhanced cellular fitness, improved mitochondrial function, and reduced sterol accumulation. Our findings identify potential modifiers and biomarkers of NPC severity, highlighting mitochondrial pathways and SLC4A5 as a therapeutic target. Impact statement Niemann-Pick type C (NPC) disease is a progressive neurovisceral lysosomal storage disorder. Here, we identified genomic modifiers of neurological resilience in an NPC family, with SLC4A5 emerging as a key biomarker and therapeutic target. Additionally, our study highlighted mitochondrial transcripts and metabolites as potential biomarkers of severity. © 2025 Federation of European Biochemical Societies.